1995
DOI: 10.2307/249709
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of IS Job Skills: A Content Analysis of IS Job Advertisements from 1970 to 1990

Abstract: Changes in the knowledge and skill requirements of information systems (IS) positions were examined by analyzing the content of advertisements for IS professionals placed in four major newspapers over the 20-year period 1970-1990. Three types of jobs were examined: programmers, systems analysts, and IS managers. The analysis of the frequency of phrases in these advertisements suggests that job ads for programmers have changed very little-technical requirements remain high, and business and systems knowledge re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
247
2
5

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(261 citation statements)
references
References 14 publications
7
247
2
5
Order By: Relevance
“…These women are both the subjects of our study and informed observers of the skills issues faced by women in the industry. As mentioned above, this study does not consider the observed skills required by women in the industry such as Todd et al (1995), instead it explores the perceived perceptions of these women.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…These women are both the subjects of our study and informed observers of the skills issues faced by women in the industry. As mentioned above, this study does not consider the observed skills required by women in the industry such as Todd et al (1995), instead it explores the perceived perceptions of these women.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…MIS professionals are expected to possess various and integrative skills and knowledge in multiple areas (Burn and Ma, 1997;Lee et al, 2002;Todd et al, 1995;Zack, 1998). "Knowledge does not come in pieces: to understand an aspect of [IS] nature is to see it through "all" the ways of imagery" (Churchman, 1971, p. 198).…”
Section: Resultsmentioning
confidence: 99%
“…The lack of awareness of the MIS concept in Vietnamese society has created a reinforcing loop that has diverted the HUE MIS curriculum emp hasis from its original intention and expectation. Third, as compared to the current model curriculum developed by leading experts in the field (Gorgone et al, 2002), HUE's MIS curriculum is lacking coverage of Interpersonal Skills, Teamwork, and Communications Skills, which are found to be the most important MIS skills by both MIS practitioners and MIS academics (Lee et al, 2002;Todd et al, 1995). This is one of the factors that prevents HUE's MIS curriculum from reaching composite interdisciplinarity (level 4).…”
Section: To Respond To the Change The Ministry Of Education And Traimentioning
confidence: 99%
“…Much of the research in IS in the last several decades has focused on identifying the technical skills required for improving the performance of business managers (Bassellier et al, 2001), the knowledge and skill requirements for programmers, systems analysts, and IT managers (Todd et al, 1995) or on assessing IT professionals' personality characteristics such as trustworthiness and credibility (Bashein & Markus, 1997). In the context of SME, the IS literature provides evidence that different levels of IT competence in the organizations studied are related to different levels of accumulated individual IT skills, knowledge and competence in the organization.…”
Section: Dragos Vierumentioning
confidence: 99%